Occurrence of aflatoxin B1 in natural products - Prado,Guilherme (2012)
The media claims for the consumption of natural resource-based food have gradually increased in both developing and developed countries. The interest in the safety of these products is partially due to the possible presence of toxigenic fungi acting as mycotoxin producers, such as aflatoxins produced during the secondary metabolism of Aspergillus flavus, A. parasiticus and A. nomius. Aflatoxins, mainly aflatoxin B1, are directly associated with liver cancer in human beings. This paper is aimed at evaluating the presence of aflatoxin B1 in a few vegetable drugs, dried plant extracts and industrialized products traded in 2010 in the city of Belo Horizonte, State of Minas Gerais, Brazil. The method used for the quantification of aflatoxin B1 was based on extraction through acetone:water (85:15), immunoaffinity column purification followed by separation and detection in high efficiency liquid chromatography. Under the conditions of analysis, the Limits of Detection and Quantification were 0.6 µg kg-1 and 1.0 µg kg-1respectively. The complete sets of analyses were carried out in duplicate. Aflatoxin B1 was noticed in a single sample (< 1.0 µg kg-1). The results revealed low aflatoxin B1contamination in the products under analysis. However, it is required to establish a broad monitoring program in order to obtain additional data and check up on the actual extension of contamination.